Analysis on Leakage Inductance and Winding Resistance of High Frequency Toroidal Transformer with Interleaved Winding and Litz Wire - Siregar, Dody Yunus Putra; Wijono; Muhammad Aziz Muslim (Faculty of Engineering, Universitas Brawijaya, 2024)
High-frequency transformers offered numerous advantages but also presented several challenges. As frequency increased, the dimensions of the transformer decreased, making parasitic parameters more dominant and unavoidable. Leakage inductance disrupted the converter circuit by storing energy that impacted the switching devices. Additionally, increased winding resistance contributed to higher winding losses, resulting in decreased transformer efficiency. This paper proposed the use of interleaved winding and litz wire as solutions to reduce parasitic parameters, such as leakage inductance and winding resistance, in toroidal transformers. Analysis and verification were conducted using 3D finite element analysis (FEA) simulations. The results demonstrated that interleaved winding significantly reduced leakage inductance by up to 98.9% as frequency increased. The distribution of leakage magnetic fields in conventional windings was effectively minimized by altering the winding arrangement. Furthermore, winding resistance was notably reduced when using litz wire, leading to a more even distribution of current density across the conductor plane, which equivalently reduced the skin effect.